Effective reduction of N2O emission via combined plasma catalysis - Li Si Ko; Ya Sheng Chen; Kuan Lun Pan; Moo Been Chang (Catalysis Communications, 2023)
N2O is a potent greenhouse gas that also causes devastating effects on the ozone layer. In this study, N2O decomposition is evaluated via thermal catalysis, plasma-alone and plasma catalysis, respectively. In thermal catalysis, N2O decomposition achieved over γ-Al2O3 catalyst is maintained at nearly 100% when operated at a temperature above 600 °C. In plasma-alone, the effects of various operating parameters were tested. As for plasma catalysis, N2O conversion can be maintained above 90% with the operating parameters controlled as applied voltage =12–22 kV, [N2O] =300 ppm and discharge gas = N2. Overall, plasma catalysis has good potential for N2O decomposition.